Assessing the Project Reading Enhancement and Development Initiatives in the New Normal for Grade-Schoolers (Readinng) Implementation: A Focus on Learners’ Reading Proficiency - Cubillas, Trixie E. (International Journal of Membrane Science and Technology, 2023)
This study intended to ascertain the pupils’ proficiency in reading after having participated in the reading intervention project “READINNG” or Reading Enhancement and Development Initiatives in the New Normal for Grade-schoolers. It utilized the Functional Literacy Assessment Tool (FLAT) for Functional Literacy Assessment tool to ascertain the level of reading performance of the pupils as well as their extent of improvement after the implementation of READINNG. There were 38 participants in the study who were the target beneficiaries of the intervention project. They are from the extension partner school of Caraga State University-College of Education. Data revealed that before the intervention, the level of proficiency of the Pupils in reading Filipino is mostly on the Nothing level, hence intervention is needed. However, after the implementation of READINNG, there are 15 pupils who can read at Paragraph Level, 8 at Story Reading level, and 5 at Story Comprehension and no one is registered at Local Material Level and none are identified as LSENs. Also, a significant improvement is found in the pupils’ level of reading proficiency in English after utilizing the Pupil Reading Intervention Materials. The data further imply that the level of proficiency of the pupils in reading in both Filipino and English increased. Hence, READINNG as intervention can improve the pupils’ level of proficiency in reading.